When a single central incisor makes the difference for human identification – a case report (Research, Society and Development, 2021)
The analysis of dental features and patterns figures amongst the primary means for human identification established by the International Criminal Police Organization (INTERPOL). Differently from fingerprint and genetic analyses, forensic dentistry does not necessarily require a minimum number of similarities between antemortem and postmortem data. In other words, human identification could be achieved from the analysis of a single distinctive tooth or even from a single dental identifier. This study aims to report a case of dental human identification of a charred body. Police investigations were carried out and narrowed the scenario towards a single victim. Fingerprints were destroyed by the fire, hence the relatives of the victim were requested to provide any antermotem dental data. A panoramic radiograph was provided. Developing third molars were visible as well as the endodontic treatment, post and core, and the nonmetallic crown of the maxillary right central incisor (tooth #11). Postmortem radiographs were taken from the cadaver and revealed the same therapeutic dental identifiers found in tooth #11. The observed similarities and the lack of discrepancies between antemortem and postmortem data converged to the positive identification of the victim. This study illustrated the importance of Forensic Dentistry for complex cases of human identification, such as those exposed to fire. Especial attention is driven to the possibility of safely achieving positive human identification with the contribution of a single distinctive tooth.